Locations of Theological Anthropology in Indonesia: A Postcolonial Literary Offer in Max Havelaar - Toar B. Hutagalung (Asosiasi Teolog Indonesia, 2021)
Colonization takes over many dimensions of life, e.g., theology, economy, history, and the idea of humanity itself (anthropology). In Indonesia, colonization by the Dutch Empire has been determining the life of the Indonesian people since the eighteenth century. The twin gazes, namely of the European orientalists and of the colonized natives, have colluded to maintain certain ruptures in the mentality of the common Indonesian person, including how they treat other human beings. Such a malforming situation is obscured from historical analysis, given what history’s very construction owes to colonial influence. To retrace a more affirming and dignified history, I look elsewhere than the formal record and, by doing so, propose that such a decolonial task lies in availing contemporaneous literary works. In this essay, I present an analysis of the colonial-era novel Max Havelaar, wherein I parse the hidden historical archive offered both in and by the text. Through this analysis, I consider how such an alternative archive affects one’s theological imaginary and promotes the (re)construction of a theological anthropology that escapes the confinement of the white Western orientalist gaze.